Beyond Diversity. A Look at the Social Integration Paths in Sport Practices - Simona Iannaccone (Culture e Studi del Sociale)
The article examines the unifying and identifying role of sport and sheds light on the paths of social integration through sports practice. The goal is to provide useful elements for the reasoning that the social sciences have played on the role of sport as a model of integration for immigrants and ethnic minorities. Reflecting on the issue of immigration necessarily leads to consider not only the numerical dimension of the phenomenon but also the socio-cultural aspects that constitute a resource and a challenge for the host country for the purposes of social integration of immigrants. However, this perspective analyzes whether sports practice can be considered primarily as a strategic resource for integration, socialization, for the consolidation of social bonds, or, on the contrary, if it generates violence and discrimination, or even if it involves experience of the denial of identity. Although the potential of sport as a strategic resource for the social integration of minorities is fully recognized, this article intends to stimulate some observations on the limits of its role and the barriers that hinder the integration of migrants and refugees into sports.